ANALISIS FAKTOR HAMBATAN SAMPING TERHADAP KAPASITAS RUAS JALAN (STUDI KASUS JALAN KAPTEN BANGSI SEMBIRING KABANJAHE) - Parada Afkiki Eko Saputra, ST,MT; Triyobi Tarigan, ST (Universitas Quality, 2021)
Kabanjahe is a city that is currently growing and increasingly in need of adequate traffic facilities, in particular Jalan Kapten Bangsi Sembiring is one of the roads that is quite dense with motorized vehicles and is in the Kabanjahe Market Center area. Roads that should be used as a means of traffic experience obstacles due to the large number of vehicles parking their vehicles on the road and other side obstacle factors, such as street vendors and cash vehicles slowing down so that traffic flow becomes disrupted and results in congestion. Given the problems on these roads, it is necessary to conduct research to determine the effect of side barriers on road capacity, to know traffic characteristics and to find possible solutions to overcome the problem of side obstacles, one of which is parking on the road at the research location. Based on the survey and analysis carried out, the volume of vehicles was at 531 pcu / hour with side activity, namely the center of the Kabanjahe city market, especially on Monday and the capacity of the road section which was filled with parking vehicles made the situation along the Captain Bangsi Sembiring road congested. the average side friction class is included in the high class (H) and experiences problems with the road segment capacity. The most influential type of side friction is caused by vehicles parked or stopped at the shoulder of the road (PSV) with a rate of 400 events / hour. One solution that can be given is by making changes in traffic management, namely installing parking barriers such as lines or cone dividers and providing prohibited signs against the direction of the road.